DIDANOSINE RETINAL TOXICITY. (December 2016) - Haug, Sara J.; Wong, Robert W.; Day, Shelley; Choudhry, Netan; Sneed, Scott; Prasad, Pradeep; Read, Sarah; McDonald, Richard H.; Agarwal, Anita; Davis, Janet; Sarraf, David
Abstract : Purpose: To report nine new cases of retinal degeneration secondary to didanosine toxicity and to summarize the previously reported cases in the literature. Methods: This was a multicenter, retrospective, observational case study from seven institutions. Medical records of patients who demonstrated well-demarcated severe midperipheral chorioretinal degeneration and who were previously treated with didanosine therapy were collected and the following information was reviewed: age, gender, medical history, detailed medication history including current and previous antiretroviral use, ocular and retinal examination findings, and multimodal imaging findings with optical coherence tomography, fundus photography, wide-field fundus autofluorescence, and wide-field fluorescein angiography. When available, findings with electrophysiology testing and automated perimetry were also collected and reviewed. A literature review was also performed to collect all reported cases of chorioretinal degeneration secondary to didanosine toxicity. Results: Nine patients were identified who had findings consistent with peripheral retinal toxicity secondary to didanosine use. Eight of the 9 patients were men, and the median age was 54 years at the time of presentation (mean: 55 years, range, 42–71 years). Snellen distance acuity ranged from 20/20 to 20/32. At least three of the cases in the series demonstrated progression of the peripheral retinal pigment epithelium and photoreceptor atrophy despite didanosine cessation. A review of the literature revealed 10 additional cases of didanosine toxicity. Seven of the 10 cases were in men (70%), and the average age was 26 years with a wide range (2–54 years). Chorioretinal findings were very similar to this cohort. Conclusion: Herein, we report the largest series of nine cases of peripheral chorioretinal degeneration secondary to didanosine toxicity in adults. When combined with the cases in the literature, 19 cases of didanosine toxicity, 4 of which occurred in children, were collected and analyzed. Three of the new cases presented showed clear progression of degeneration despite didanosine cessation. Newer nucleoside reverse transcriptase inhibitors may potentiate mitochondrial DNA damage and lead to continued chorioretinal degeneration. Abstract : Herein, the authors report the largest series of nine cases of peripheral chorioretinal degeneration secondary to didanosine toxicity in adults. When combined with the cases in the literature, 19 cases of didanosine toxicity, 4 of which occurred in children, were collected and analyzed. Three of the new cases presented showed clear progression of degeneration despite didanosine cessation. Newer nucleoside reverse transcriptase inhibitors may potentiate mitochondrial DNA damage and lead to continued chorioretinal degeneration.